QUESTIONS OF INFORMATIONAL SECURITY OF KHERSON STATE UNIVERSITY. - A. Mazur; I. Svetlanov (Kherson State University, 2009)
The article deals with problems of informational security of modern organizations and analyzes relevant questions of computer security at Kherson State University.